QUERCETIN AND PIPERINE CONTENT OF FRACTION N-HEXANE : ETHYL ACETATE SESEWANUA LEAF (CLERODENDRUM FRAGRANS WILD.) - Imran, Arlan; Zulfiayu; Ahmad Aswad (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2025)
Sesewanua (Clerodendrum fragrans Wild.) is used as an anti-inflammatory (anti-rheumatoid arthritis) topically and orally and as an antioxidant with very strong potential. The n-hexane fraction: ethyl acetate of sesewanua leaves contains secondary metabolites of flavonoids and alkaloids. This study aimed to measure the levels of the flavonoid quercetin and the levels of the alkaloid piperine in the n-hexane: ethyl acetate fraction of the ethanol extract of sesewanua leaves. This research method: The n-hexane:ethyl acetate fraction was determined for its flavonoid content at a wavelength of 256 nm and piperine alkaloids at a wavelength of 342.5 nm using the UV-Vis spectrophotometry method. The results obtained from the n -hexane:ethyl acetate fraction of the ethanol extract of sesewanua leaves contained the flavonoid compound quercetin as much as 6.385 PPM and the alkaloid compound piperine as much as 5.854 PPM. Conclusion: The statistical results of the Independent T. Test show that there are significant levels of the flavonoid quercetin and alkaloid piperine, which means that the levels of the flavonoid quercetin in the n-hexane: ethyl acetate fraction of the ethanol extract of sesewanua leaves are higher than the alkaloid piperine compound.